The Perspective of People Receiving Food Support - Even-Zohar, Ahuva (Journal of Applied Business and Economics, 2021)
The research examines the perspective of Israelis assisted by Non-governmental organization (NGOs) to promote their food security. This qualitative study employed the Interpretive Phenomenological Approach. The sample consisted of 16 recipients of food support aged 33-62, and they were interviewed in-depth semistructured protocol. Five main themes emerged: The background of food insecurity; Forms of food support; The experience of receiving food support; The effect of the assistance on food security; and the responsibility for food security. The participants indicated that the state welfare system should be responsible for food security, and they prefer payment cards that enable them to purchase food suitable to their individual needs while maintaining their dignity. Although the support provided does not entirely extricate families from food insecurity, they gain confidence by being able to receive food in times of hardship. The findings indicate the importance of considering the opinions of those in need when making policy decisions regarding food security.